1998
DOI: 10.1902/jop.1998.69.8.879
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin and Lactoferrin Levels in the Gingival Crevicular Fluid of Children

Abstract: The purpose of this study was to determine the levels of calprotectin and lactoferrin, 2 microbiostatic proteins, in the gingival crevicular fluid (GCF) of normal children. The children represented a population, primarily underprivileged, seeking care at a regional dental health care center. GCF was collected from Ramfjord teeth (or their deciduous equivalent). GCF volume was quantified by conductance. Calprotectin and lactoferrin levels were quantified by sandwich ELISA, and found to have a mean value of 70.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
2
16
1
Order By: Relevance
“…11,[29][30][31][32][33][34][35][36][37][38][39][40][41] Examples of the inflammatory states in which extracellular calprotectin reportedly increases are depicted in Table 1. The calprotectin-upregulated pathological states were also listed in more detail in a review by Johne et al 21) Berntzen et al reported that in healthy human serum/ plasma, the concentration of calprotectin was less than 1 mg/ml, while the plasma concentration of patients with rheumatoid arthritis (RA) was reportedly increased to approximately 10-fold higher concentrations as mean values.…”
Section: Pathological States In Which Calpro-tectin Is Upregulatedmentioning
confidence: 99%
“…11,[29][30][31][32][33][34][35][36][37][38][39][40][41] Examples of the inflammatory states in which extracellular calprotectin reportedly increases are depicted in Table 1. The calprotectin-upregulated pathological states were also listed in more detail in a review by Johne et al 21) Berntzen et al reported that in healthy human serum/ plasma, the concentration of calprotectin was less than 1 mg/ml, while the plasma concentration of patients with rheumatoid arthritis (RA) was reportedly increased to approximately 10-fold higher concentrations as mean values.…”
Section: Pathological States In Which Calpro-tectin Is Upregulatedmentioning
confidence: 99%
“…So far, only a few studies have focused on the role of calprotectin in periodontitis. Calprotectin can be found in the gingival crevice fluid (83, 86, 116, 121, 136), showing elevated levels in patients with periodontitis (82, 106, 107). Calprotectin has also been found incorporated in dental calculus (81).…”
Section: Use Of Calprotectin In the Diagnosis Of Inflammatory Bowel Dmentioning
confidence: 99%
“…Interestingly, calprotectin release can be induced in neutrophils and monocytes by stimulation with lipopolysaccharide from P. gingivalis , and also from Prevotella intermedia and Actinobacillus actinomycetemcomitans , in a dose‐dependent manner (80, 156). On the other hand, in children with various degrees of gingivitis, calprotectin proved to have a negative correlation with the amount of gingival crevice fluid (116). On the basis of these findings the diagnostic significance of calprotectin as an indicator of periodontal disease activity, in contrast to neutrophilic granule components such as myeloperoxidase and elastase, was questioned (116).…”
Section: Use Of Calprotectin In the Diagnosis Of Inflammatory Bowel Dmentioning
confidence: 99%
“…It is well established that proteins with antimicrobial activity, like lysozyme or calprotectin, are major components of the oral defense (16–18). A more recent observation is that human epithelia at mucosal surfaces secrete peptide antibiotics (1, 14, 17, 19, 20).…”
mentioning
confidence: 99%